2004
DOI: 10.1161/01.res.0000109416.56608.64
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Mitochondrial Complex I Activity in Ischemic/Reperfused Rat Heart

Abstract: Abstract-Reactive oxygen species (ROS) are considered an important factor in ischemia/reperfusion injury to cardiac myocytes. Mitochondrial respiration is an important source of ROS production and hence a potential contributor to cardiac reperfusion injury. In this study, we have examined the effect of ischemia and ischemia followed by reperfusion of rat hearts on various parameters related to mitochondrial function, such as complex I activity, oxygen consumption, ROS production, and cardiolipin content. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
268
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(294 citation statements)
references
References 56 publications
20
268
2
4
Order By: Relevance
“…43 However, neither increased peroxide production, oxidative damage to proteins or lipids, nor elevation of oxidative stress defense mechanisms were found, with the exception of increased immunocytochemical staining of MnSOD. We do not have a clear-cut explanation for these discrepant results, but in the absence of any other indication for the development of reactive oxygen species, we hypothesize that the increased staining of MnSOD is not directly involved in an oxidative stress response.…”
Section: Discussionmentioning
confidence: 94%
“…43 However, neither increased peroxide production, oxidative damage to proteins or lipids, nor elevation of oxidative stress defense mechanisms were found, with the exception of increased immunocytochemical staining of MnSOD. We do not have a clear-cut explanation for these discrepant results, but in the absence of any other indication for the development of reactive oxygen species, we hypothesize that the increased staining of MnSOD is not directly involved in an oxidative stress response.…”
Section: Discussionmentioning
confidence: 94%
“…Ischemia/reperfusion-induced oxidative stress has a noticeable influence on NADH-ubiquinone reductase (complex I) activity, since it transitorily diminishes it (Paradies et al 2004). Complex II activity is also robustly reduced by reperfusion-induced oxidative stress (Pasdois et al 2006;Chen et al 2008) via deglutathionylation of its 70-kDa flavin protein and tyrosine nitration by peroxynitrite (Chen et al 2007(Chen et al , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…ONOO Ϫ -mediated inactivation of complex I increases O 2 ⅐ Ϫ production from that location, and O 2 ⅐ Ϫ generated by complex I is released exclusively into the matrix (16,51,(63)(64)(65). Animal I/RP models showed that, upon RP, the ETC complex activities are reduced, complex I is the main source of mitochondrial ROS (2,31,54), and NO derived from endothelial NOS (eNOS) is the one responsible for ONOO Ϫ formation, inhibition of complex I activity, and suppression of tissue O 2 consumption (84).…”
mentioning
confidence: 99%